2009
DOI: 10.1242/jcs.033951
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of clathrin-independent endocytosis

Abstract: There is good evidence that, in addition to the canonical clathrin-associated endocytic machinery, mammalian cells possess multiple sets of proteins that are capable of mediating the formation of endocytic vesicles. The identity, mechanistic properties and function of these clathrin-independent endocytic pathways are currently under investigation. This Commentary briefly recounts how the field of clathrin-independent endocytosis has developed to date. It then highlights recent progress in identifying key prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
210
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(217 citation statements)
references
References 124 publications
6
210
1
Order By: Relevance
“…Further analysis revealed that centers of clathrin-coated and caveolar vesicles were ~130 nm apart ( Figure 3C). (2) By using transmission electron microscopy, we observed morphologically characteristic clathrin-coated pits and caveolae (the flaskshaped membrane invagination) at the plasma membrane as previously described [30,31]. The partially fused caveolar and clathrin-coated vesicles were also observed ( Figure 3D).…”
Section: Fusion Of Clathrin-coated Vesicles and Caveolar Vesicles Undsupporting
confidence: 74%
“…Further analysis revealed that centers of clathrin-coated and caveolar vesicles were ~130 nm apart ( Figure 3C). (2) By using transmission electron microscopy, we observed morphologically characteristic clathrin-coated pits and caveolae (the flaskshaped membrane invagination) at the plasma membrane as previously described [30,31]. The partially fused caveolar and clathrin-coated vesicles were also observed ( Figure 3D).…”
Section: Fusion Of Clathrin-coated Vesicles and Caveolar Vesicles Undsupporting
confidence: 74%
“…28 Endocytic pathways have been mainly classified as clathrin-dependent or -independent, 28 the later can be further classified as dynamin-dependent orindependent pathway. Dynamin is a large GTPase directly involved in pinching off endocytic vesicles from the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Many NCE pathways have been reported, including caveolar-type endocytosis, CLIC/GEEC-type endocytosis, the putative flotillin-associated endocytic structures, phagocytosis, macropinocytosis, dorsal ruffles (or waves), and entosis [62,63]. Caveolar-type endocytosis is the best studied NCE.…”
Section: Clathrin-dependent and Clathrin-independent Endocytic Pathwaysmentioning
confidence: 99%
“…Clathrinindependent endocytosis itself has been further dissected into seemingly distinct pathways, based on the reliance of these pathways on certain proteins and lipids, their differential drug sensitivities and their abilities to internalize particular cargos [134]. Many NCE pathways have been reported including caveolar-type endocytosis, CLIC/GEEC-type endocytosis, the putative flotillin-associated endocytic structures, phagocytosis, macropinocytosis, dorsal ruffles (or waves), and entosis [62,63]. New evidence suggests that EGF-induced EGFR endocytosis may also be mediated by NCE.…”
Section: Endocytosis Of Egfrmentioning
confidence: 99%